The Utilisation of a Mobile Phone Forum on the Winksite application in the teaching and learning of History: A case study of Pre-service Teachers at Makerere University (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The teaching and learning process is becoming a big challenge at Higher Education Institutions in Sub-Saharan Africa. This is mainly due to the constraints created by the liberalisation of university education and the implied surge in student numbers. In the area of History education particularly, the challenge of large student numbers has forced lecturers to predominantly use behaviourist teaching methods such as lecture and recitation. These methods are characterised by constrained dialogical conversations between lecturers and students, memorising of History facts, dates and limit students’ capacity to think historically, which in turn compromises the quality of learning about the past. This article argues for the use of Mobile phone forums as lenses from the present that afford dialogical construction of meanings about the past. A qualitative approach with a case study design was used limited to pre-service teachers (students) at the Makerere University, Uganda. A Critical Discourse Analysis was used to analyse the qualitative data obtained from the students’ engagement on the Mobile phone forum by means of the winksite application. The key research findings demonstrated that mobile phone forums enhance interactions between lecturers-students, students-students as a helpful precondition for collaborative learning and reflection about the human past. Conclusions was drawn with a recommendation for History educators to embrace mobile phone forums as a sustainable innovation at the African higher educational context with a potential to enhance dialogical conversations between the past the present and the anticipated future.
Keywords: Critical Discourse Analysis; History teaching and learning; Interactivity; M-Learning; Mobile phone forums; Winksite application